Cost-effective defined medium for the production of polyhydroxyalkanoates using agricultural raw materials. (October 2015) - Suwannasing, Waranya; Imai, Tsuyoshi; Kaewkannetra, Pakawadee
Highlights: Application of novel substrate of pineapple for producing PHAs biopolymer. Alternative approach to the fermentation process of pineapple into PHAs biopolymer. Pineapple as a carbon source showed competitive price among agricultural substrates. Achievement of cost saving defined medium containing sugar based material. The improvement of fermentation process without pH-control. Abstract: According to the cost of carbon substrate for producing biopolymer of polyhydroxyalkanoates (PHAs) still has a barrier to extend in an industrial scale. The aim of this work was to evaluate the defined PHAs media containing the agricultural raw materials of pineapple and sugarcane to produce PHAs by Bacillus strain. Batch fermentation was carried out in flask scale to compare the efficiency of defined media using statistical methodology. The defined medium 8 of pineapple was achieved the highest PHAs concentration and productivity (1.86 g/L and 0.077 g/Lh). The effect of pH and aeration was extensively studied in a fermentor. The results were revealed that PHAs production would be increased from the condition of uncontrolled pH and at higher aeration rate. The extracted PHAs clearly showed in a homopolymer structure of poly(3-hydroxybutyrate) (PHB) with melting temperature ( T m ) of 172 °C 54.39% crystallinity.